Sistem Pendukung Keputusan Pemilihan Peserta Olimpiade Karya Ilmiah Tingkat Nasional Menggunakan Metode SAW - Achmad Fikri Sallaby; Venny Novita Sari; Rizka Tri Alinse (Jurnal Sistem Komputer dan Informatika (JSON), 2021)
Participants of the national level scientific work olympic are participants who will take part in competitions between one campus and another on a national basis in showing scientific works or research results with certain themes in a competition. The importance of choosing is because an olympic participant is a pride and also brings the good name of the college where they study, if you bring the wrong participant it will create new problems in assessing the quality of a university, in this study, the selection of participants for the olympic scientific work at the national level using concept of the algorithm of a decision support system using the MOORA method. The MOORA method or the abbreviation of Multi-Objective Optimization on The Basis Of Ratio Analysis is a decision support system method that has simple stages and processes in solving problems. The results of this study found the highest score with the candidate with a value of 10.93991.